Use of UGC-Infonet Journals by the Faculty Members, Research Scholars and Students of Manonmaniam Sundaranar University, Tirunelveli: A Study - Baladhandayutham, A. (Journal of Information and Knowledge, 2014)
This study deals with the use of UGC-Infonet journals among the Faculty members, Research scholars and Students of Manonmaniam Sundaranar University. 80.91 per cent of the respondents are aware about the UGC-Infonet journals. 33.63 per cent of the respondents know about Infonet journals from library professionals. Nearly one third of respondents access the Infonet journals daily. 77.27 per cent of the respondents need the orientation programme for the effective use of Infonet journals. More than half of the respondents access the Infonet journals for their research/project work. Majority of the respondents report that limited access terminals is the main problem for accessing Infonet journals. 75.46 per cent of the respondents are satisfied with use of UGC-Infonet journals.